2003
DOI: 10.5187/jast.2003.45.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Recombinant Human Lactoferricin Culture as a Substitute for Antibiotic in Pig Starter Diets

Abstract: Sixty [(Duroc×Yorkshire)×Landrace] pigs (7.63±0.41kg average body weight and 25-d average age) were used in a 20-d growth assay to determine the effect of dietary recombinant human lactoferricin culture (RHLC) supplementation on growth performance, digestibility and plasma IgG concentration in weaning pigs. Dietary treatments included 1) Negative control (NC : without antibiotic), 2) Positive control (PC : NC diet + 0.1% chlortetracycline), 3) RHLC0.3 (NC diet + 0.3% RHLC), 4) RHLC0.5 (NC diet + 0.5% RHLC). No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Therefore, they are suitable as feed additive for livestock and poultry. Recent research of AMP supplementations has demonstrated that AMP could increase the growth performance of piglets (Hong, Kim, Kwon, & Hwang, 2003; Tang et al., 2009; Yoon et al., 2012) and broilers and reduce the number of intestinal pathogens of chickens (Wang et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are suitable as feed additive for livestock and poultry. Recent research of AMP supplementations has demonstrated that AMP could increase the growth performance of piglets (Hong, Kim, Kwon, & Hwang, 2003; Tang et al., 2009; Yoon et al., 2012) and broilers and reduce the number of intestinal pathogens of chickens (Wang et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 1711 AMP have been identified from a wide range of organisms (; accessed February 2011). Recent research demonstrated that AMP could improve the growth performance of piglets ( 4 , 5 ) , growing–finishing pigs ( 6 ) , chickens ( 7 ) and fishes ( 8 ) , and the integrity of intestinal surfaces and intestinal mucosal response of chickens ( 7 , 9 , 10 ) . It seems that AMP are suited to be alternatives to AGP, but the use of AMP from natural sources is not at present cost-effective.…”
mentioning
confidence: 99%
“…Consequently, new concepts have been developed aiming to promote animal health and to secure growth performance, feed efficiency, and product quality as well. Several naturally occurring compounds have been shown to affect the composition and activity of the microflora in the gastrointestinal tract of pigs such as diet acidification (Tsiloyiannis et al, 2001), mannan-oligosaccharides (Ko et al, 2000), herbs (Wenk, 2003), minerals (Hill et al, 2001), direct-fed microbial (Xuan et al, 2001) and lactoferricin (Hong et al, 2003). Recently, livestock industry has been interested in egg yolk antibody as nonantibiotic feed additives.…”
Section: Methodsmentioning
confidence: 99%